1993
DOI: 10.1073/pnas.90.14.6776
|View full text |Cite
|
Sign up to set email alerts
|

An unusual RNA tertiary interaction has a role for the specific aminoacylation of a transfer RNA.

Abstract: The nucleotides in a tRNA that specifically interact with the cognate aminoacyl-tRNA synthetase have been found largely located in the helical stems, the anticodon, or the discriminator base, where they vary from one tRNA to another. The conserved and semiconserved nucleotides that are responsible for the tRNA tertiary structure have been shown to have little role in synthetase recognition. Here we report that aminoacylation of Escherchia coli tRNACYS depends on the anticodon, the discriminator base, and a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 34 publications
1
106
3
Order By: Relevance
“…Only the influence of 29-deoxy groups was further characterized kinetically with chemically synthesized halves, ligated enzymatically to full tRNAs containing single 29-deoxy groups at the positions suggested by the interference assay (Table 1)+ Inhibition was observed for all but the dU29-containing tRNA, which showed a slight increase of k cat /K m relative to the allribo ligated tRNA+ This remains unexplained+ The extent of inhibition was most obvious at A76, the 39 terminal nucleotide where the amino acid will be attached+ Considering that the synthetase is a class II type, attaching the amino acid to the 39 hydroxyl, this finding confers significance to the presence of the 29 hydroxy group (Arnez & Moras, 1997)+ A 5-6-fold decrease is seen, except for U25, for positions C74, C36, and G34 in the acceptor stem and in the anticodon loop, both regions interacting with the synthetase (in the yeast system, Ruff et al+ (1991); in the E. coli system, D+ Moras, pers+ comm+)+ An approximate threefold reduction in charging was seen for C67, A58, and A24+ For the other positions the effect was smaller+ In conclusion, it is observed that single 29-deoxy substitutions had, in general, only a minor effect on charging and the effect is well below the losses in aminoacylation efficiency found for base changes of the discriminator nucleotides (Giegé et al+, 1993)+ This observation agrees with earlier results with E. coli tRNA Ala and E. coli tRNA Pro , which, however, had been analyzed using minihelices or tRNAs assembled from fragments (Musier-Forsyth & Schimmel, 1992;Liu & Musier-Forsyth, 1994;Yap & MusierForsyth, 1995)+ In contrast, multiple occurrences of 29-deoxy modifications in at least one half of E. coli tRNA Asp resulted in a dramatic decrease of charging, with the exception of the dA series+ The half harboring the more important interference positions showed the stronger inhibition+ This cumulative effect of 29-deoxy groups has been observed for other tRNAs or tRNA fragments (Khan & Roe, 1988;Perreault et al+, 1989;Musier-Forsyth & Schimmel, 1992;Yap & Musier-Forsyth, 1995; Aphasizhev et al+, 1997)+ An explanation for these observations might be that the presence of several 29-deoxy functions causes a conformational effect incompatible with productive interaction with the enzyme+ A difference in conformation for the yeast tRNA Asp containing any one of the four nucleotides entirely as the 29-deoxy derivative has indeed been verified experimentally (Aphasizhev et al+, 1997)+ The loss of charging activity found by these authors after complete replacement of uridines or guanosines by their 29-deoxy analogues was attributed to a specific effect of U11 and G27 on the basis of the X-ray structure of the complex (Cavarelli et al+, 1993)+ This is an unusually strong effect caused by one position+ It was not found in the present analysis for position 27 and only to a smaller extent at position 11+ A functional difference from the otherwise related yeast system is one explanation+ However, the involvement of several more deoxy positions contributing ...…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Only the influence of 29-deoxy groups was further characterized kinetically with chemically synthesized halves, ligated enzymatically to full tRNAs containing single 29-deoxy groups at the positions suggested by the interference assay (Table 1)+ Inhibition was observed for all but the dU29-containing tRNA, which showed a slight increase of k cat /K m relative to the allribo ligated tRNA+ This remains unexplained+ The extent of inhibition was most obvious at A76, the 39 terminal nucleotide where the amino acid will be attached+ Considering that the synthetase is a class II type, attaching the amino acid to the 39 hydroxyl, this finding confers significance to the presence of the 29 hydroxy group (Arnez & Moras, 1997)+ A 5-6-fold decrease is seen, except for U25, for positions C74, C36, and G34 in the acceptor stem and in the anticodon loop, both regions interacting with the synthetase (in the yeast system, Ruff et al+ (1991); in the E. coli system, D+ Moras, pers+ comm+)+ An approximate threefold reduction in charging was seen for C67, A58, and A24+ For the other positions the effect was smaller+ In conclusion, it is observed that single 29-deoxy substitutions had, in general, only a minor effect on charging and the effect is well below the losses in aminoacylation efficiency found for base changes of the discriminator nucleotides (Giegé et al+, 1993)+ This observation agrees with earlier results with E. coli tRNA Ala and E. coli tRNA Pro , which, however, had been analyzed using minihelices or tRNAs assembled from fragments (Musier-Forsyth & Schimmel, 1992;Liu & Musier-Forsyth, 1994;Yap & MusierForsyth, 1995)+ In contrast, multiple occurrences of 29-deoxy modifications in at least one half of E. coli tRNA Asp resulted in a dramatic decrease of charging, with the exception of the dA series+ The half harboring the more important interference positions showed the stronger inhibition+ This cumulative effect of 29-deoxy groups has been observed for other tRNAs or tRNA fragments (Khan & Roe, 1988;Perreault et al+, 1989;Musier-Forsyth & Schimmel, 1992;Yap & Musier-Forsyth, 1995; Aphasizhev et al+, 1997)+ An explanation for these observations might be that the presence of several 29-deoxy functions causes a conformational effect incompatible with productive interaction with the enzyme+ A difference in conformation for the yeast tRNA Asp containing any one of the four nucleotides entirely as the 29-deoxy derivative has indeed been verified experimentally (Aphasizhev et al+, 1997)+ The loss of charging activity found by these authors after complete replacement of uridines or guanosines by their 29-deoxy analogues was attributed to a specific effect of U11 and G27 on the basis of the X-ray structure of the complex (Cavarelli et al+, 1993)+ This is an unusually strong effect caused by one position+ It was not found in the present analysis for position 27 and only to a smaller extent at position 11+ A functional difference from the otherwise related yeast system is one explanation+ However, the involvement of several more deoxy positions contributing ...…”
Section: Discussionmentioning
confidence: 94%
“…Aminoacylation reactions were carried out in 50 mM HEPES, pH 7+5, 30 mM KCl, 20 mM MgCl 2 , 2+5 mM ATP, and 77 mM L-U-14 C-aspartic acid (213 mCi/mmol, Amersham, UK) at 37 8C with tRNA transcripts or ligated tRNAs between 0+16 and 6+4 mM and a fixed synthetase concentration of 0+0062 units in a total volume of 60 ml as described in Sampson and Uhlenbeck (1989)+ Kinetic parameters, as the average of at least two independent experiments, were derived from LineweaverBurk or Michaelis-Menten plots using KaleidaGraph software+ Deviation was 620%+ K cat /K m values for ligated tRNAs were determined either from Lineweaver-Burk plots or from plots of rate-versus-tRNA concentration (Segel, 1975;Hou et al+, 1993)+…”
Section: Aminoacylation Kineticsmentioning
confidence: 99%
“…The severe impairment of tRNA QSer_C9/A13 in glutaminylation suggests an important role for a presumed 9-13-22 base triple in recognition of tRNA QSer by GlnRS+ In tRNA Ser , this base triple is composed of the three purines G9-G13-A22, whereas in the class I tRNA Gln a The five most common nucleotide combinations for each structural element are shown+ Data are compiled for all nonmitochondrial elongator tRNAs+ The total number of sequences analyzed is 1,385 for class I and 353 for class II+ b Secondary structures for two class I tRNAs are ambiguous such that the assignment of nucleotide 9 is not included+ Class II selenocysteine tRNAs possess additional nucleotides between the acceptor and D-stems; for these species, the identity of the nucleotide directly 39 to position 8 is compiled+ c This number includes six selenocysteine tRNAs and five tRNAs of other specificity (Fig+ 5)+ d The nomenclature for D-loop structure follows Giege et al+ (1993), in which a and b represent the number of nucleotides present 59 and 39 to the conserved guanosines at positions 18 and 19+ Nucleotides 13 and 22 are considered to be part of the D-stem, regardless of whether they form a Watson-Crick pair+ the triple at the analogous position is A45-A13-A22 (Fig+ 1)+ To evaluate whether purines are needed at these positions to maintain structure, we again examined the tRNA sequence database (Sprinzl et al+, 1998; Table 2)+ This analysis shows that of 353 class II sequences, cytidine is present at position 9 in only five tRNAs and the C9-A13-A22 triple in tRNA QSer_C9/A13 is present in only three+ There are also only eleven examples of uracil at position 9 in class II tRNAs+ These sequences were examined to assess whether a pyrimidine at position 9 in class II tRNAs might require a compensating structural feature elsewhere in the molecule (Fig+ 5)+ The alignments show that nearly all such class II tRNAs possess at least one unpaired nucleotide 39 to the variable stem, adjacent to the augmented D-stem (nucleotide C48 is paired with G15 in the Levitt interaction; Fig+ 1)+ Interestingly, this nucleotide is conserved as a uracil+ The only exceptions to this are several of the very unusual selenocysteine species' tRNA Sec , which possess unpaired nucleotides 59 to the The correlation of Py9 with unpaired nucleotides adjacent to C48 provides further insight into the requirements for folding in class II tRNAs+ It appears that a purine at position 9 may be crucial for adequate stacking on the base at position 21, which is also very highly conserved as a purine (Fig+ 1, Table 2)+ Thus, a pyrimidine at position 9 may destabilize the structure owing to a decreased favorable free energy of base stacking+ Alternatively, it is possible that Py9 may form fewer or weaker hydrogen bonds within a 9-13-22 base triple than could be formed by a purine+ Because tRNA QSer_C9/A13 retains a large D-loop, it is not immediately evident how additional nucleotides, located between U47q and C48 (Fig+ 1), might help reconstitute the structure+ One plausible hypothesis is that these class II tRNAs possess a class I-like 9-12-23 triple instead of the class II 9-13-22 triple+ Further rearrangements would then be required, to permit one or more of the unpaired nucleotides to stack inside the core region, stabilizing the fold+ Model building and energy minimization should be helpful in evaluating the possibilities+ Such studies might be helpful in providing a hypothesis for why the unpaired base is conserved as a uracil+…”
Section: Importance Of the 9-13-22 Base Triplementioning
confidence: 99%
“…In tRNA QSer_C9/A13 , a pyrimidine at position 9 without the additional unpaired variable loop nucleotide produces a very low proportion of functional transcripts after refolding in the presence of Mg 2ϩ (Table 1)+ The stability of the molecule (Fig+ 3) suggests that it may fold into an alternative stable conformation+ No global alteration to the fold is suggested, however, from a secondary structure prediction algorithm (data not shown), so that the differences from native tRNA may be fairly localized+ GlnRS interacts directly with the 59 side of the D-stem and adjacent D-loop nucleotides but not with discriminating groups on the bases of C9 or A13+ Thus, the very strong effect on k cat is likely manifested via an indirect effect on the enzyme-RNA backbone contacts, ultimately resulting in mispositioning or destabilizing the tRNA acceptor end in the active site+ The k cat effect is unusual because the mutation of nucleotides involved in tRNA architecture often results instead in significant increases in K m (Perret et al+, 1992;Puglisi et al+, 1993;Rogers & Soll, 1993;Frugier et al+, 1994)+ Strong effects on k cat are normally associated with the mutation of identity nucleotides in direct contact with the enzyme (Giege et al+, 1993), although an extreme disruption of the yeast tRNA Asp D-loop/T-loop contacts did substantially lower k cat as well (Puglisi et al+, 1993)+…”
Section: Importance Of the 9-13-22 Base Triplementioning
confidence: 99%
See 1 more Smart Citation